Spleen Damage in Coronavirus Infection - Saidov Akmal Abdullaevich (Research Parks Publishers, 2022)
According to statistics, 96% of those with severe COVID-19 have lymphopenia, that is, a decrease in the absolute number of lymphocytes in the blood. One of the reasons is the ability of SARS-CoV-2 to directly affect the tissues of lymphoid organs: the spleen and lymph nodes of the mediastinum, which was proven during the autopsy of deceased patients. In addition, it has been proven that coronavirus can affect lymphocytes and induce their apoptosis through signaling pathways. The mechanisms of spleen damage in COVID-2019 are poorly understood. This review focuses on spleen damage in coronavirus infection.